(untitled) (International Journal of Engineering and Computer Science, 2013)
Reliability for functioning units is essential, be it on the parts of memory chips of computers, software or hardware or it can be on the part of heavy machinery in any industrial system. Reliability analysis can give excellent results to improve the maintainability and portability of management design for existing and future product. Extensive reviews of two-component repairable system models have been presented by Lie et al(1977) and Yearout et al. (1986). In all these models, it is assumed that failure times and repair times of the components are independent. In this paper, Reliability analysis of a system having one main unit and two supporting units is proposed, assuming that the system fails whenever the main unit fails and system shuts down whenever either both the supporting units fail or main unit and one of the supporting units fail. To improve the reliability of the system, concept of preventive maintenance is also added. Using regenerative point technique various system parameters such as Transition Probabilities, Mean sojourn times, Mean time to system failure, Availability, Busy period of repairman in repairing the failed units etc. are calculated. At last profit analysis is also done. In this paper, failure time distributions are taken to be negative exponential whereas the repair time distributions are arbitrary.